KEANEKARAGAMAN JENIS ANGGREK (ORCHIDACEAE) DI AREA HUTAN BUKIT KUKUS, BANGKA BARAT - Djodi Surya Prawira; Eka Yuliawati; Erika Purba (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2019)
Orchid is a group of flowering plants of the Orchidaceae family with a total of 700-800 genera and 25,000-35,000 species. Identification of orchids is a step to determine orchid species by comparing the morphological characteristics of each orchid found. This research was conducted in Bukit Kukus, Air Belo Village, Muntok Subdistrict, West Bangka Regency for four days, from March 9 to March 12, 2018 using exploration methods, including: a preliminary survey, data collection and herbarium making. The results showed that the number of orchids that were found was the conclusion that could be drawn from this exploration is in Bukit Kukus, Air Belo Village, Muntok District, West Bangka Regency, found 15 types of orchids, consisting of 7 genera, namely Agrostophyllum, Arachnis, Bulbophyllum, Coelogyne, Dendrobium, Nephelaphyllum and Poystachya with the most genera Bulbophyllum found, up to 5 species. The most common orchids are found in Zone I, where 12 of the 15 species can be found, while the most common type of orchid is epiphytic orchids with rock substrates.